Thamnīap ʻongk̨̄on phāk ʻēkkachon ph̄ưa kānp̨̄ongkan læ k̄ækhai panhā yāsēptit (Samnak Nayōbāi læ Ph̄æn, Samnakngān P̨̄o. P̨̄o. S̨̄o., 1998)
Directory of public interest non-government organizations in Thailand working on drug abuse problems and preventions.